Estágio supervisionado em música: articulando conhecimentos na construção da docência - Sperb, Leonardo Martins (2017)
This research was developed in the Graduate Program in Education of the Federal University of Santa Maria, research line Education and Arts (LP4), together with the group Formação, Ação e Pesquisa em Educação Musical (FAPEM) and sought to understand how trainees articulate knowledge musical and pedagogical-musical in the construction of teaching in Music in the Supervised Stage (ES) I and II. Through a case study (YIN, 2005), direct observations and participants and semi-structured and focus group interviews were carried out with six trainees attending ES I and II, in pairs, developed in Early Childhood Education. The data produced from these sources of evidence were analyzed according to the Discursive Textual Analysis (MORAES; GALLIAZZI, 2011), and could be understood from four categories and respective theoretical references: a) the academic-professional formation in the degree course in Music of the UFSM (CERESER, 2003; BRASIL, 2004; MATEIRO, 2009; WIELEWICK, 2010; BAUMER, 2012); b) the ES in Music and its senses (MATEIRO; TÉO, 2003; GATTI, 2010; PIMENTA; LIMA, 2010; BELLOCHIO, 2011; KHAOULE, CARVALHO, 2012; NATERA, 2013); In this paper, we describe the practice of ES in pairs, called peer teaching (SAWFFORD, 1998;; HAYAMA, 2008;; AZEVEDO, 2008), and in the context of children's education and their relations with music (KISHIMOTO, 2002; WERLE, 2010; GOELZER; (1988). It was concluded that trainees feel a distancing between the musicological, pedagogical and pedagogical-musical disciplines of the Licenciatura in Music course, a perception that makes it difficult for them to relate the musical and pedagogical-musical knowledge developed in these curricular components. The senses attributed to ES induce trainees to seek to reproduce teaching models or to seek technical instrumentation for teaching in ES, and the specificity of Early Childhood Education in relation to the child's development makes it difficult for academics to develop, at this stage of teaching, the musical contents that come learning in the course and would like to teach, which causes them to problematize the identities of the Music teacher. Finally, peer teaching enables the articulation of knowledge to occur, as trainees divide their assignments, one of which assumes musical activities (singing and playing) and other pedagogical-musical activities (interacting with children).